GGE biplot analysis for visualization of mean performance and stability for seed yield in taramira at diverse locations in India (Journal of Oilseed Brassica, 2026)
Among different oilseeds, taramira or rocket salad (Eruca sativa L.) is an important non- edible oilseed crop cultivated in arid and semi-arid parts of India. It is cultivated on marginal areas where sowing gets delayed or cultivation of other crops is not feasible. However, its low yield and varietal instability across environments is not encouraging to make it competitive with other crops. Thus development of genotypes having high seed yield with stable performance is of paramount importance. In the present investigation six genotypes of rocket salad viz., TMB 2006-2, T 27, TMB 2008, RTM 1146, RTM 314 and RTM 1212 were grown at Bawal (Haryana), Bathinda (Punjab), Bikaner (Rajasthan), Jobner (Rajasthan), Sriganganagar (Rajasthan) and Navgaon (Rajasthan) during rabi (post-rainy) season of 2008-09. Data recorded on seed yield were subjected to GGE biplot analyses, which revealed that total sums of squares of variation were 78.73% for environments (E), 7.67% for genotypes (G) and 13.60% for genotype by environment interactions (GE). It was demonstrated that seed yield of RTM 1212> T 27> TMB 2006-2>TMB 2008> RTM 314, while RTM 1146 was lowest yielder. However, RTM 1146 was the most stable genotype across the locations followed by TMB 2006-2 and T 27. RTM 314 and TMB 2006-2 were found to be least stable while RTM 1212 was moderately stable for seed yield. Exploitation of G coupled with GE revealed that RTM 1212 was the winner genotype with respect to its performance at Bikaner, Bathinda, Jobner and Sriganganagar locations while T 27 was identified as the winner genotype at Bawal and Navgaon . GGE biplot analyses also elucidated that owing to its high mean performance, RTM 1212 may prove a better donor over RTM 1146 for transferring stability genes